Goal setting, personality traits, and the role of insurers and other service providers for Swiss Millennials and Generation Z - Carlo Pugnetti; Pedro Miguel Henriques; Ulrich Moser (Journal of Risk and Financial Management, 2022)
Service providers are developing more sophisticated offerings, and it is important for them to understand the demographics and specific context by which individuals might procure their services. This allows companies to stay relevant to their customers. The target of this paper is to investigate the types of goals Millennials and Generation Z individuals are pursuing and what role different service providers may play in supporting these endeavors, with the aim of providing actionable insights for insurers. Furthermore, it is to investigate how personality traits may relate to differences in individuals' preferences. The study is based on a survey of 854 Swiss university students. The results indicate that goals are concentrated in a few categories, and educational institutions and healthcare providers are well-positioned to support goal achievement. Insurers, on the other hand, rank low among the preferences, and their profile is largely undifferentiated. This result indicates that insurers need to further focus their efforts to gain relevance among younger customers. Supporting goals relating to self-fulfillment and ability for high-conscientious and/or low-honest/humble customers by focusing on risk education and risk management seems a particularly interesting strategy for insurers.
Keywords: 650; goal types; insurance services; personality traits